EFEKTIFITAS LAYANAN KONSULTASI DALAM MEMBANTU KONSULTI MENGENTASKAN MASALAH PIHAK KETIGA - Sari, Nofla Ilfa (Bimbingan dan Konseling, 2014)
This research was motivated by the duties and responsibilities of counselor in the obligate consulting services in performing consulting services that have not been effective. The focus of this study to describe: planning, implementation, evaluation, analysis ofthe results ofthe evaluation, and implementation of the follow-up consultation services. This research was conducted with a qualitative descriptive. As for the informantsare: counselor, homeroom teacher, subject teachersand students.Instruments that researchers usein this study are interviews, a technique used in the processing of data through data reduction, data presentation and conclusion. The results of this study reveal the already effective planning. On the implementation has not been effective because the teacher is not able to encourage and train the konsulti in solving third party problem. At the completion of the evaluation has not been seen by athird-party problemby konsulti. In the analysis of the evaluation result the counselor know from the observation result about development of a third party and at follow-up session the counselor conduct individual counseling. Based on the results of the study recommended to counselor, homeroom teacher and subject teachers to work together on alleviate studentsâ problem so that students can be effective in carrying out their activities.